Groundswell Part 2 : Acting on Internal Climate Migration - Clement, Viviane; Rigaud, Kanta Kumari; de Sherbinin, Alex; Jones, Bryan; Adamo, Susana; Schewe, Jacob; Sadiq, Nian; Shabahat, Elham (World Bank, Washington, DC, 2021)
This sequel to the Groundswell report includes projections and analysis of internal climate migration for three new regions: East Asia and the Pacific, North Africa, and Eastern Europe and Central Asia. Qualitative analyses of climate-related mobility in countries of the Mashreq and in Small Island Developing States (SIDS) are also provided. This new report builds on the scenario-based modeling approach of the previous Groundswell report from 2018, which covered Sub-Saharan Africa, South Asia, and Latin America. The two reports’ combined findings provide, for the first time, a global picture of the potential scale of internal climate migration across the six regions, allowing for a better understanding of how slow-onset climate change impacts, population dynamics, and development contexts shape mobility trends. They also highlight the far-sighted planning needed to meet this challenge and ensure positive and sustainable development outcomes. The combined results across the six regions show that without early and concerted climate and development action, as many as 216 million people could move within their own countries due to slow-onset climate change impacts by 2050. They will migrate from areas with lower water availability and crop productivity and from areas affected by sea-level rise and storm surges. Hotspots of internal climate migration could emerge as early as 2030 and continue to spread and intensify by 2050. The reports also finds that rapid and concerted action to reduce global emissions, and support green, inclusive, and resilient development, could significantly reduce the scale of internal climate migration.